Validity and reliability of the 3-minute all-out test in national and international competitive swimmers - Piatrikova, E.; Sousa, A. C.; Gonzalez, J. T.; Williams, S. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To assess the concurrent and predictive validity of the 3-minute all-out test (3MT) against conventional methods (CM) of determining critical speed (CS) and curvature constant (D') and to examine the test-retest reliability of the 3MT in highly trained swimmers. Methods: Thirteen highly trained swimmers (age 16 [2] y, weight 64.7 [8.5] kg, height 1.76 [0.07] m) completed 4 time trials and two 3MTs over 2 wk. The distance-time (DT) and speed-1/time (1/T) models were used to determine CS and D' from 4 time trials. CS3MT and D ' 3MT D3MT' were determined as the mean speed in the final 30 s of 3MT and as the speed-time integral above CS, respectively. Results: CS3MT (1.33 [0.06] m/s) did not differ from CSCM (1.33 [0.06] m/s, P>.05) and correlated nearly perfectly with CSCM (r=.95, P<.0001). D ' 3MT D3MT' (19.50 [3.52] m) was lower than D ' DT DDT' (23.30 [6.24] m, P<.05) and D ' 1/T D1/T' (22.15 [5.75] m, P=.09). Correlations between D ' 3MT D3MT' and D ' CM DCM' were very large (r=.79, P=.002). CS and D' between the two 3MT trials were not different (CS mean change=-0.009 m·s-1, P=.102; D' mean change=0.82 m, P=.221). Correlations between the two 3MT trials were nearly perfect and very large for CS (r=.97) and D' (r=.87, P<.05), respectively, with coefficients of variation of 0.9% for CS and 9.1% for D'. Conclusion: The 3MT is a valid protocol for estimation of CS and produces high test-retest reliability for CS and D' in highly trained swimmers.